1983
DOI: 10.1037/0735-7044.97.5.738
|View full text |Cite
|
Sign up to set email alerts
|

Sodium appetite elicited by intracerebroventricular infusion of angiotensin II in the rat: I. Relation to urinary sodium excretion.

Abstract: Intracerebroventricular infusion of angiotensin II (Ang II) elicits a substantial sodium appetite in the rat. The present results demonstrate that this phenomenon consists of a small, early phase of sodium ingestion that is not the result of prior sodium loss but that thereafter urinary excretion of sodium exceeds intake and consequently the animals become hyponatremic and hypovolemic. The larger and more sustained bouts of sodium ingestion occurring 8-12 hr after the start of the Ang II infusion appear to rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 10 publications
3
37
1
Order By: Relevance
“…These effects were described by many researchers (Fluharty and Manaker, 1983;Unger et al, 1989;Weekley, 1992;Fitzsimons, 1998;Ferguson et al, 2001;Geerling and Loewy, 2008). In addition, in the present work it was found that ANG II i.c.v.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…These effects were described by many researchers (Fluharty and Manaker, 1983;Unger et al, 1989;Weekley, 1992;Fitzsimons, 1998;Ferguson et al, 2001;Geerling and Loewy, 2008). In addition, in the present work it was found that ANG II i.c.v.…”
Section: Resultssupporting
confidence: 77%
“…Furthermore, studies in mammals have demonstrated that i.c.v. ANG II administration enhanced renal sodium excretion, water and sodium intake (Fluharty and Manaker, 1983;Unger et al, 1989;Ferguson et al, 2001), increased vasopressin and oxytocin secretion and decreased plasma renin activity (Weekley, 1992;Ferguson et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…While circulating AngII tends to retain sodium by a direct renal action, 9 as well as through aldosterone release from the adrenal gland, stimulation of brain AngII receptors has been reported to induce natriuresis. 10 In 1983, Fluharty and Manaker [19] demonstrate that i.c.v. infusion of AngII elicits a small, early phase of sodium appetite that is not the result of prior sodium loss, but that thereafter urinary excretion of sodium exceeds intake and consequently the animals become hyponatraemic and hypovolaemic.…”
Section: Discussionmentioning
confidence: 99%
“…There is a good amount of evidence in the literature that manipulation of ANGII levels alters thirst in rats that are hydrated [8, 9]demonstrating that ANGII is directly involved in eliciting dipsogenic behavior. Some evidence also exists on the role that ANGII plays in the induction of salt appetite [4, 10, 11], although the onset of salt appetite after application of ANGII occurs much later than that of thirst [51]. It is clear nevertheless that administered ANGII promotes a series of physiological and behavioral responses whereby water and sodium are retained or released, and water and salt is ingested, respectively.…”
Section: Discussionmentioning
confidence: 99%